Pengaruh Pemberian Limbah Cair Tahu Dan Fotoperiod Terhadap Kadar Glukosa Pada Kultivasi Mikroalga Scenedesmus sp. - Dian Larasati; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
More energy needs are met from fossil energy, but that fuel can’t be renewed. Various studies have been conducted to utilize microalgae as raw material for biofuels. The carbohydrate content in microalgae can be used as raw material for bioethanol. Scenedesmus sp. considered a promising microalgae for biofuel production because it has a high level of growth and glucose production, and can utilize organic matter as a nutrient in the form of tofu liquid waste so that the synergy between wastewater treatment and biomass production can run well. The purpose of this study was to determine the optimal conditions for growth of Scenedesmus sp. with the influence of photoperiod and volume of tofu wastewater on glucose levels formed after the cultivation process. In this study variations in the provision of tofu wastewater in the cultivation medium (0%, 20%, 40%, 60%, 80%, 100%) with the ratio of photoperiod light:dark (16:8, 14:10, 12:12, and 24:0) and the time of data collection on days are 0, 1, 3, 5, 7, 9, 11, and 13. Based on the results of the study obtained the highest glucose level of 36,41 mg/l at the added of 20% tofu liquid waste and photoperiod 12:12. Keywords: Glucose, tofu liquid waste, photoperiod, Scenedesmus sp.